Decision Support System for Determining Flood Evacuation Locations in Kabupaten Bandung Using the Simple Additive Weighting (SAW) Method - Rani Gusti Angesti; Arieftyarto Taufik Ramadhan; Fifin Nur Hanifah; Grace Agustina; Afrin Fauzya Rizana; Amelia Kurniawati (Jurnal Ilmiah Teknik Industri, 2022)
West Java Province is one of the provinces with the most flood disasters, which is 863 times and the highest number of floods occurred in Kabupaten Bandung is 228 times. Because floods often occur in Kabupaten Bandung make BPBD (Badan Penanggulangan Bencana Daerah) must respond to this problem, including by choosing a quick evacuation location. Choosing an appropriate evacuation route is very helpful in reducing losses and especially saving people's lives. So we need a computer-based system that can help BPBD in determining which location is most suitable as an evacuation location in Kabupaten Bandung by using the SAW (Simple Additive Weighting) method. This method is a simple weighting method or additional weighting to solve problems in a decision support system. The results of this study are a rank of recommendations for evacuation locations in Kabupaten Bandung. To test the feasibility and suitability of the system, a BlackBox test and user acceptance test was carried out.